Kekuatan Mekanis Antibacterial Resin Campuran Titanium Dioksida - Budiprasojo, Azamataufiq; Erawantini, Feby (Jurnal Rekayasa Mesin, 2021)
The aim of this research is to analyze the effect of Titanium Dioxide (TiO2) nanoparticles as resin concentrate on mechanical strength. The tested mechanical strength is Bending strength, Impact Strength, and Microhardenest Strength. The types of resin used in this study were acrylic resin without conventional modification and acrylic resin with an additional 0.01 gr and 0.06 gr of TiO2. Specimen dimensions are made revered to ISO 20795-1 (2008) standard specifications. Mechanical strength was determined by using the universal testing machine, Izod pendulum impact testing machine, and also Vickers microhardness tester. From the analysis, the researcher found that the bending strength of resin acrylic was greatly decreased by increasing the TiO2 concentration. It happens in both TiO2 0.01gr and 0.06gr of acrylic resin compared to the non TiO2 resin. The impact strength of 0.01gr TiO2 acrylic resin was significantly increased compared to non TiO2 acrylic resin. But on the other hand for 0.06gr acrylic resin, impact strength was decreased and recorded the lowest impact strength. The highest Micro hardness strength was found in 0.06gr TiO2, It is significantly increased compared to 0.01gr TiO2 and 0gr TiO2. The general conclusion is, adding 0.01gr TiO2 nanoparticles as concentrated into acrylic resin can significantly increase the bending strength, bending strength, and microhardness strength. Meanwhile, adding 0.06gr Tio2 nanoparticles as concentrated into acrylic resin can only increase the bending strength and the microhardness strength, but not for its impact strength.